DIAGNOSIS TIROID (Diagnosis of Thyroid) - Liong Boy Kurniawan; Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Thyroid disease often causes unspecific or mild symptoms, so laboratory tests are needed to confirm the functional diagnosis of thethyroid disorder. The laboratory tests which are important to establish the diagnosis of thyroid disorder include: total and free thyroidhormones, its related (thyroid) hormone binding proteins and auto antibodies. The thyroid hormone tests are mostly measured withcompetitive or sandwich immunoassays and each method can be interfered by several factors. Some drugs may increase or decrease thethyroid functional tests and several factors such as: underlying diseases, age, pregnancy, occurrence of heterophil antibody and autoantibodies may also interfere the thyroid tests results. The interpretation of an unusual combination from thyroid stimulating hormonesuch as free thyroxin and tri-iodothyronine results needs confirmation of underlying condition for establishing the right diagnosis. Thisreview is aimed to evaluate several factors which may influence the thyroid tests and interpretation.